Сецесія в мистецтві Буковини - Міщенко, І. (Студії мистецтвознавчі, 2008)
This article explores the peculiarity of manifestation of the art in time of secession in Bukowina. It is possible to follow the different stages this styles development in architecture, fine art and decorative and applied art in the region, but features of Art Nouveau appear irregular in different kinds of arts.